Determination of CCT due to interconnected link tripping using the OMIB and EAC - Salim, Nur Ashida; Jasni, Jasronita; Ab Wahab, Norfishah; Ab Aziz, Nur Fadilah; Rahmat, Nur Azzammudin; Mat Yasin, Zuhaila; Mohamad, Hasmaini (Science Publishing Corporation, 2018)
This paper presents an algorithm to determine the critical clearing time (CCT) due to the effect of interconnected link tripping by applying the one machine infinite bus (OMIB) equivalent system method and equal area criterion (EAC). This paper also proposes the implementation of graphical user interface (GUI) to monitor and predict the CCT from time to time. The CCT is defined as the highest time interval by which the fault is expected to be cleared with the aim of maintaining the electricity supply stability. The computation of important numerical development of CCT is deduced from the entails three fault situations, which are; pre-fault, during fault and post-fault situations, with the main focus on pre-fault situation. The CCT becomes significantly shorter whilst transient instability is induced by a three-phase fault occurred at the bus bar next to the substation connected with a sensitive generator. It is sufficient to maintain the transient stability albeit fault occurred at other locations by setting the protection relay with the computed value of CCT. A circuit breaker which is installed and operated before the smallest CCT will not affect the transient instability throughout the occasion of fault. The IEEE Reliability Test System 1979 (IEEE RTS-79) is used to verify the accuracy of the proposed methodology in determining the CCT.